Meta-Analysis the Effect of Hormonal Contraception on the Weight Gain and Hypertension in Women of Reproductive Age - Kusumaningtiyas, Zonna Aditiya; Tamtomo, Didik; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Hormonal contraception is a contraceptive method that can prevent pregnancy because it contains estrogen and progesterone. The use of hormonal contraception for a long time can cause side effects including increased body weight, cholesterol deposits, and hypertension. The purpose of this study was to examine, analyze, and estimate the magnitude of the effect of the use of hormonal contraception on the incidence of weight gain and hypertension in women of childbearing age based on the results of previous similar studies. Subjects and Method: This study is a systematic review and meta-analysis using PRISMA flowchart diagrams. The process of searching for articles was carried out between 2004-2021 using 3 databases, including Google Scholar, PubMed, and Science Direct. The keywords used in the database search are